PROSEDUR DOKUMENTASI TRANSFER PRICING PT. A BERDASARKAN PERATURAN MENTERI KEUANGAN NO. 213 - Fambia Noor Azizah, (2020)
This Final Project Report discusses how the transfer pricing documentation procedure is carried out by PT. A based on the Minister of Finance Regulation (PMK) Number 213. Transfer pricing documents are made for the purpose of fulfilling the Taxpayer's obligation to make and save these documents if there are any transactions with side whom has a special relation. The transfer pricing documentation procedure is carried out by explaining the process of making the transfer pricing document that is made by PT. A and the contability with PMK-213. In the presence of the transfer pricing document, the transaction that is done by PT. A with side whom has special relation can be said to be reasonable if it can be proven by making the transfer pricing document. Based on the result of transfer pricing document that is made by PT. A, the implementation can be said as a whole in accordance with PMK-213. It is just that there is some uncleared informations and not listed in transfer pricing document that is created by PT. A. However, this deficiency didn't cause fatal thing to the contents of PT. A's tranfer pricing document.